Identification of Linearized Regions of Non-Linear Transducers Responses - Abdul Wahab, Deji; Khan, Sheroz; Chebil, Jalel; Musse, Mohamud Ahmed; Ahmed Wathik, Naji; Al-Kaissi, -; Alam, A. H. M. Zahirul (2010)
Transducers have found wide applications in industries, though, they possess nonlinear responses. The nonlinearity feature does not prevail over the entire range; rather there are sections (or regions) on the response curves that are easily regarded as linear. This work focuses on analyzing transducer characteristics by finding regions exhibiting larger level of linearity.The point of inflection is a joint between two consecutive linear segments, and it is where changes in the output signal in response to external parameter variations remain at minimum compared to its immediate neighboring points. It is shown through simulations on how, assuming that a given system does not operate over the entire range of the response curve, a linear response is assured. This is done by translating the circuit operating over the linear section by employing additional external circuit elements. This paper attempts at analyzing a transducer characteristics by showing regions around the points of inflections where variations remain most linear.